Effectiveness of Local Anesthetic Nerve Block compared with Spinal Anesthesia in cases of Rhomboid excision and Limberg flap closure for Pilonidal Disease - Bakhsh, Khuda; Javed, Nida; Iqbal, Ejaz; Samee, Umair; Sehrish, Anam; Cheema, Khalid Mehmood; Iqbal, Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Modified Limberg Flap (MLF) is regarded as the mainstay of treatment for Sacrococcygeal Pilonidal disease due to less postoperative complications as compared to other available surgical procedures. This Operative procedure can be performed under Spinal anesthesia as well as Local Anesthesia. Aim: To compare outcome of patients undergoing Modified Limberg Flap for Sacrococcygeal pilonidal sinus under Local anesthesia with adrenaline versus Spinal anesthesia in terms of post-operative pain, Seroma formation & Hospital stay. Methods: This was a randomized controlled clinical trial conducted at Department of Surgery, Sughra Shafi Medical Complex, Narowal. Study was conducted for a period of 06 months and 80 patients were included through non-probability consecutive sampling technique. Patients were randomly divided into 2 equal groups by computer generated method. Patients in group LA underwent MLF under Local anesthesia with adrenaline while patients in group SA underwent MLF under Spinal anesthesia. Informed written consent was obtained from all the participating patients. Results: Mean age of all patients was 24.78±5.12 years. Minimum and maximum age of patients was 16 and 37 years respectively. Gender distribution shows that 96.25% were male while 3.75% were female. Seroma formation in Group-LA was 0% while in Group-SA, it was 7.5%. Hospital stay of patients in Group-LA and in Group-SA was 9.60±9.39 and 29.10±9.37 hours respectively. Mean operation time in Group-LA was 42±5.64 minutes whereas in Group-SA mean operation time was 46±7.53 minutes. Mean pain score in Group-LA was 2±1.04 at 12th hour of surgery and in Group-SA it was 3.83±1.06 at 12th hour of surgery. Conclusion: It is concluded that Modified Limberg Flap can be performed under local anesthesia as a day case procedure to save time, reduce work burden and cost of surgery.